Implementation of The "Element of Surprise" Concept in The Development of Sustainable Tourism Attractions in Rural Community-based Tourism Destination - Setiawan Priatmoko; Yitno Purwoko; Erna Wigati; Lóránt Dénes Dávid (Journal of Tourism and Economic, 2026)
This study examines the application of the "Element of Surprise" concept as a strategic innovation in developing tourism village attractions while maintaining sustainable tourism principles. In a highly competitive tourism market, tourism villages should present not only authentic but also memorable and unique experiences for visitors. Through a qualitative descriptive approach, this research explores how unexpected events, hidden spots, and unique interactive activities can be engineered to trigger positive emotions and memorable experiences (memorable tourism experiences). The results demonstrate that integrating the element of surprise with local knowledge and environmental conservation significantly enhances visitor satisfaction. Crucially, this positive emotional response potentially promotes powerful word-of-mouth marketing without compromising the destination's unique cultural and ecological characteristics. This model provides a practical framework for tourism village managers to design creative, low-cost, high-impact attraction programs.